Raoul Wallenberg in Budapest : myth, history and Holocaust - Levine, Paul Ansel (Vallentine Mitchell, 2010)
Introduction: Framing the Issues -- Myth, History and the Historian's Social Responsibility -- A Life before Budapest: Wallenberg's Background, Personality and Motives -- March 1944: The Holocaust in Hungary, An Overview -- April-May: Swedish Diplomacy in Budapest Prior to Wallenberg's Arrival -- June: Myth and Fact: Understanding Wallenberg's Recruitment and Mission -- July: Wallenberg Arrives in Budapest -- Summer 1944: Per Anger, Archbishop Erling Eidem and the 'Everyday' Politics of Genocide -- August: Valdemar Langlet and Carl Ivan Danielsson, the Forgotten Swedes -- September: The Calm before the Storm -- October: Raoul Wallenberg Enters History -- November-December: Death, Despair and Heroism -- January 1945: The End of Diplomacy and Freedom -- Epilogue: 17 January 1945: Wallenberg Leaves History and Enters Myth